Influence of sample volume on nitrate N and O isotope ratio analyses with the denitrifier method. (22nd December 2021) - Zhou, Mengyang; Granger, Julie; Chang, Bonnie X.
Abstract : Rationale: Analyses of the isotope ratios of nitrogen ( 15 N/ 14 N) and oxygen ( 18 O/ 16 O) in nitrate (NO3 − ) with the denitrifier method require relatively high sample volumes at low concentrations (≤1 μM) to afford sufficient analyte for mass spectrometry, resulting in isotopic offsets compared to more concentrated samples of the same isotopic composition. Methods: To uncover the origins of isotopic offsets, we analyzed the N and O isotope ratios of NO3 − reference materials spanning concentrations of 0.5–20 μM. We substantiated the incidence of volume‐dependent isotopic offsets, then investigated whether they resulted from (a) incomplete sample recovery during N2 O sparging, (b) blanks – bacterial, atmospheric, or in reference material solutions – and (c) oxygen atom exchange with water during the bacterial conversion of NO3 − to N2 O. Results: Larger sample volumes resulted in modest offsets in δ 15 N, but substantial offsets in δ 18 O. N2 O recovery from sparging was less complete at higher volumes, resulting in decreases in δ 15 N and δ 18 O due to associated isotope fractionation. Blanks increased detectably with volume, whereas oxygen atom exchange with water remained constant within batch analyses, being sensitive to neither sample volume nor salinity. The sizeable offsets in δ 18 O with volume are only partially explained by the factors considered in our analysis. Conclusions: Our observations argue for bracketing of NO3 − samples with reference materials that emulate sample volumes (concentrations) to achieve improved measurement accuracy and foster inter‐comparability.